Meningioma Infiltrative Accompanied by Organic Delusional Disorders - Ahmad Asmedi (Scientia Psychiatrica, 2021)
Introduction: Meningiomas are primary extra-axial tumours of the central nervous system (CNS) with an incidence of 2 in 100,000 in adults. There is an estimate of a 3: 1 female predominance of these tumours mainly due to the action of estrogen. Meningiomas are commonly associated with headaches, imbalances, visual disturbances, and other neurological problems which can be very debilitating. This case report will describe a case of a brain tumour accompanied by psychiatric disorders. Case presentation: Mrs. W, a 37 years old woman, a housewife, Javanese, Moslem, married, and lower socioeconomic background, came with her family to the Neurology polyclinic because she experienced changes in behavior seven months ago in the form of much silence, daydreaming, cannot communicate, sometimes talking to herself, eating drinking and bathing must be helped and served. Four months before being admitted to the hospital, the patient's headaches worsened and the patient became increasingly withdrawn, accompanied by weakness in both legs. From the results of CT-scan with contrast, the results showed that the meningioma infiltrates and perifocal oedema, which caused subfalcine herniation as far as 2.73 cm to the right. Conclusion: Infiltrative meningioma is often accompanied by mental disorders in the form of personality changes, depressive-like symptoms and neurological symptoms. Clinicians should be able to detect a brain mass so that management can be undertaken immediately.